LAW ENFORCEMENT OF COPYRIGHT AS AN EFFORT TO STRENGTHEN THE CREATIVE ECONOMY - Kanti Rahayu; Moh. Taufik (Adisam Publisher, 2024)
The Indonesian state is currently aggressively developing the creative economy sector so that it can increase rapidly in supporting the country's economic growth. To be able to realize a creative economy that can support the country's economic growth, legal enforcement of intellectual rights (property rights) is needed, one of which is protecting and enforcing statutory regulations regarding Copyright.This research aims to find out how the law is enforced against the Copyright Law in Indonesia in order to strengthen the creative economy and what are the obstacles in realizing law enforcement against Copyright in Indonesia. This type of research is library research. The data source used in this research is secondary data. Data collection techniques are carried out through conventional and online searches. Innovative works that emerge as part of the creative economy must be protected under copyright law, so that the Indonesian creative economy can make a significant contribution to the national economy. The main problem with weak legal enforcement of the copyright law is in terms of substance, structure and legal culture.